Ano-uro-genital mucosal melanoma UK national guidelines. (August 2020) - Smith, Henry G.; Bagwan, Izhar; Board, Ruth E.; Capper, Sharon; Coupland, Sarah E.; Glen, Jessica; Lalondrelle, Susan; Mayberry, Antonia; Muneer, Asif; Nugent, Karen; Pathiraja, Pubudu; Payne, Miranda; et al.
Abstract: Ano-uro-genital (AUG) mucosal melanomas are rare cancers associated with poor outcomes and limited evidence-based management. The United Kingdom AUG mucosal melanoma guideline development group used an evidence-based systematic approach to make recommendations regarding the diagnosis, treatment and surveillance of patients diagnosed with AUG mucosal melanomas. The guidelines were sent for international peer review, and are accredited by The National Institute for Health and Clinical Excellence (NICE). A summary of the key recommendations is presented. The full documents are available on the Melanoma Focus website. Highlights: Mucosal melanomas of ano-uro-genital structures are rare malignancies with poor prognoses. Owing to their rarity, there is limited evidence in the literature to guide clinical decision making. We provide a summary of the evidence and recommendations for the management of AUG melanoma.